Predicted Shifts in the Distributions of Atlantic Reef-Building Corals in the Face of Climate Change - Principe, Silas C.; Acosta, André L.; Andrade, João E.; Lotufo, Tito M. C. (Frontiers in Marine Science, 2021)
Many species drive the diversity of ecosystems by adding structural complexity to the environment. In coral reefs, stony corals act as habitat-forming species, increasing niche availability for other organisms. Some coral species play key roles as reef builders due to their abundance or morpho-functional characteristics. Thus, changes in the distributions of these species can entail cascading effects in entire ecosystems. With climate change, many coral species are experiencing shifts in their distributions, threatening the preservation of coral reefs. Here, we projected the current and future distributions of three key reef builders of the Atlantic (Mussismilia hispida, Montastraea cavernosa, and the Siderastrea complex) under three relative concentration pathway scenarios: the most optimistic, the most pessimistic and one moderate scenario (RCP2.6, 4.5, and 8.5). Our models revealed that all the above species will undergo habitat loss in the future (2100) in the most pessimistic scenario, although new areas could become suitable, including regions in the eastern Atlantic Ocean. Additionally, when considering only its actual range of occurrence, M. hispida will lose habitats under all future scenarios. Moreover, in some regions of both the Tropical Northwestern Atlantic (TNA) and the Brazilian coast, these three species could disappear, with detrimental consequences for the associated communities. We highlight the need for an urgent change of course to guarantee functional reefs in the Atlantic in the future.